Educational Problems in Indonesia in the Excitement of Building the Golden Generation 2045 - Ferdianto, Muhammad (Raudhah Publisher, 2024)
The preamble to the Constitution of the Republic of Indonesia in 1945 is a reference for great ideals so that this nation's ideology is created. In Indonesia itself, the fourth paragraph of the preamble to the Constitution of the Republic of Indonesia in 1945 has the goal of